Annona emarginata (Schltdl.) H. Rainer 'araticum-de-terra-fria' cultivada com variação de nitrogênio: produtividade e perfil químico dos voláteis foliares - Campos, Felipe Girotto [UNESP] (2014)
The species Annona emarginata (Schltdl.) H. Rainer 'araticum-de-terra-fria' has great potential as a rootstock for this hybrid atemoya (Annona cherimola Mill. X Annona squamosa L.) conferring resistance to stem borer. This resistance may be related to primary and secondary metabolisms. Nitrogen is an essential element on the synthesis of amino acids, proteins such as Ribulose 1,5 - diphosphate (Rubisco), nucleic acids, chlorophyll, secondary metabolites, and other important cellular constituents. Besides these functions, it should be considered competing relation to CO2 by reducing agents and carbon skeleton. Therefore, the present study aimed to evaluate the influence of variation in the level of nitrogen in the nutrient solution on yield and composition of the leaf volatile during the early development of seedlings of A. emarginata. To study the productivity gas exchange were evaluated, the activities of nitrate reductase, catalase, peroxidase, superoxide dismutase, lipid peroxidation, the dry weight of roots, stems and leaves, leaf area, stem diameter ratio leaf area, net assimilation rate, relative growth rate, leaf specific weight, dry weight distribution to different organs of the plant, leaf mass ratio and the composition of volatiles extracted from the leaves. Plants grown with intermediate levels of nitrogen had higher carboxylation efficiency and CO2 assimilation rate. Nitrate reductase activity varied with different levels of nitrogen that the plants were submitted. In the largest amount of nitrogen, plants with lower productivity, demonstrated competition between nitrogen fixation, CO2 assimilation and synthesis of terpenes. The activity of antioxidant enzymes prevented lipid peroxidation in plants subjected to different levels of nitrogen. Gas exchange, the activity of nitrate reductase and antioxidant enzymes in plants grown with 78.75 and 118.12 mg L-1 N contributed their best ...